PENGARUH HARGA, KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN (Studi Pada Pelanggan Banaran 9 Resto Coffe and Tea Semarang) - Lilin Fajriatus Indriyanti, 15.05.51.0240; Liana, Lie (Students' Journal of Economic and Management, 2019)
This study aims to test and analyze the effect of price, product quality and service quality on customer satisfaction. The location in this study was at Banaran 9 coffee and tea restaurant Semarang. The population in this study were Banaran 9 customers coffee and tea Semarang restaurants, because the population is very large, this study uses a sample of 100 respondents. The sampling technique with purposive sampling data collection method. The purposive sampling criteria is that you have been a customer for at least 1 year and have income. The data used in this study is primary data, with a questionnaire as a research instrument. Data is processed with SPSS version 19 and the tools used are multiple linear regression, validity test, reliability test, F test, determination coefficient test (R2), and t test. The results of the study show that the price variable does not affect customer satisfaction, product quality and service quality have a positive and significant effect on customer satisfaction.